New optical solitons of conformable resonant nonlinear Schrödinger’s equation - Rezazadeh Hadi; Abazari Reza; Khater Mostafa M. A.; Inc Mustafa; Baleanu Dumitru (Open Physics, 2020)
Sardar subequation approach, which is one of the strong methods for solving nonlinear evolution equations, is applied to conformable resonant Schrödinger’s equation. In this technique, if we choose the special values of parameters, then we can acquire the travelling wave solutions. We conclude that these solutions are the solutions obtained by the first integral method, the trial equation method, and the functional variable method. Several new traveling wave solutions are obtained including generalized hyperbolic and trigonometric functions. The new derivation is of conformable derivation introduced by Atangana recently. Solutions are illustrated with some figures.